I love you the purplest - Joosse, Barbara M.; Whyte, Mary (San Francisco, Calif : Chronicle Books, 1996)
Two boys discover that their mother loves them equally but in different ways.
Keywords: Brothers -- Fiction; Mothers and sons -- Fiction; Fishing -- Fiction